2017
DOI: 10.1080/0167482x.2017.1308350
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward menopause, sexual function and depressive symptoms in Mexican women

Abstract: The objective of this study was to explore the beliefs and attitudes toward menopause, depressive symptoms and sexual function in both premenopausal and postmenopausal Mexican women. The Beliefs about and Attitudes toward Menopause Questionnaire, the Female Sexual Function Index and the Center for Epidemiologic Studies Depression Scale were answered by 253 women between the ages of 46 and 59 years. Negative attitudes toward menopause were associated with a more depressive symptomatology, but there was no assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
4
7
0
2
Order By: Relevance
“…Although it was determined that the sexual quality of life of the women in the study group was moderate, women with severe menopausal symptoms had a lower sexual quality of life than other women. Our study result is consistent with the literature (Marvan et al, 2018; Thomas & Kamath, 2017) and suggests that menopause affects sex life negatively. It is important to raise awareness among healthcare professionals on planning activities that would improve the sexual quality of life of postmenopausal women.…”
Section: Discussionsupporting
confidence: 93%
“…Although it was determined that the sexual quality of life of the women in the study group was moderate, women with severe menopausal symptoms had a lower sexual quality of life than other women. Our study result is consistent with the literature (Marvan et al, 2018; Thomas & Kamath, 2017) and suggests that menopause affects sex life negatively. It is important to raise awareness among healthcare professionals on planning activities that would improve the sexual quality of life of postmenopausal women.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the current study confirmed that the attitude towards post-menopause period is one of the main predictors of sexual satisfaction. Similarly, the research by Marvan et al, on Mexican women, exhibited that positive attitudes towards premenopausal and postmenopausal periods are associated with better sexual function (33). The results of a meta-analysis by Bahari et al, on 3453 participants suggested that 25% and 58% of Iranian women had respectively positive and neutral attitudes towards menopause, indicating the poor sexual knowledge among this population (34).…”
Section: Discussionmentioning
confidence: 86%
“…Postmenopausal female sexual dysfunction is a complex disorder that has many causes [ 1 ]. Reasons for these negative changes in sexual function may include biological (e.g., decreased sex hormones), psychological (e.g., the development of mood symptoms), interpersonal (e.g., sexual dysfunction in the sexual partner), and socio-cultural (e.g., negative gender stigma in older women) factors [ 1 , 8 , 14 ].…”
Section: Introductionmentioning
confidence: 99%